Luminescent (metallo-supramolecular) cross-linked lanthanide hydrogels from a btp (2, 3-bis(1, 2, 3-triazol-4-yl)picolinamide) monomer give rise to strong Tb(iii) and Eu(iii) centred emissions. (31st January 2023) - Hegarty, Isabel N.; Bradberry, Samuel J.; Lovitt, June I.; Delente, Jason M.; Willis-Fox, Niamh; Daly, Ronan; Gunnlaugsson, Thorfinnur
Abstract : The synthesis and study of the lanthanide luminescent 2, 3-bis(1, 2, 3- triazol-4-yl)picolinamide (btp ) based hydrogels F1 and F2 is described where Tb(iii ) or Eu(iii ) are also used to crosslink the btp units within the polymers. Abstract : The development of the 2, 3-bis(1, 2, 3- triazol-4-yl)picolinamide (btp ) ligand 2, from the amine 1 (which was also structurally characterised) possessing a methyacrylamide unit that facilitated the co-polymerisation of this btp ligand into polymeric hydrogels, using 2-hydroxyethyl methacrylate (HEMA), methylmethacrylate (MMA) and ethylene glycol dimethacrylate (EGDMA), is described, resulting in the formation of two polymers with two different concentrations (cast as polymeric films), F1 (0.03 wt%) and F2 (0.3 wt%), respectively, These polymers were then used to form luminescent soft-materials using lanthanide ions, which can coordinate to the btp ligands; the focus herein on the latter polymer was shown to be more luminescent. The non-polymerisable ligand 3, possessing an acetamide moiety was also developed as a model compound. We also present the formation of a soft material (a supramolecular hydrogel) from the precursor 1, which was shown to be thermoreversibly formed, and its morphological and rheological properties were probed. We also show that upon addition of Tb(iii ), to this supramolecular gel, we have interrupted the soft-material features upon coordination of the ion to the btp ligands. While the focus herein is on the F2, in both cases the metal ion coordination (which was achieved upon hydration of the polymers in solutions of these ions) results not only in the formation of a luminescent material (Tb(iii ) is known to give rise to highly luminescent green emission upon coordination of the ion to btp ligands), but also in the instantaneous formation of metal mediated crosslinking within the polymeric matrix. The photophysical properties of both 2 and 3 are presented, both in solution, and as in the case of 2, after the polymerisation within the hydrogel; which in the case of Tb(iii ) results in the formation of green emitting polymers, clearly visible to the naked eye. Similarly, we demonstrate that upon using Eu(iii ), red emission is observed from polymer F2 .